1998
DOI: 10.1345/aph.17297
|View full text |Cite
|
Sign up to set email alerts
|

Drug and Environmental Factors Associated with Adverse Pregnancy Outcomes Part I: Antiepileptic Drugs, Contraceptives, Smoking, and Folate

Abstract: Adequate prepregnancy planning is essential for women who have epilepsy. Women receiving folate-lowering drugs may be at increased risk of adverse pregnancy outcomes. Therefore, epileptic women contemplating pregnancy should be treated with the minimum number of folate-lowering drugs possible and receive folic acid supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
8

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 151 publications
0
33
0
8
Order By: Relevance
“…Folic acid deficiency has been postulated as a possible cofactor in the teratogenic effects associated with the maternal use of AEDs during pregnancy [13,18,31,33].…”
Section: Discussionmentioning
confidence: 99%
“…Folic acid deficiency has been postulated as a possible cofactor in the teratogenic effects associated with the maternal use of AEDs during pregnancy [13,18,31,33].…”
Section: Discussionmentioning
confidence: 99%
“…Folate deficiency has long been recognized as an important contributor to susceptibility for birth defects (Lewis et al, 1998;Lucock, 2000) and epidemiological studies have demonstrated a beneficial effect of folate supplementation on prevention of birth defects (Berry and Li, 2002;Czeizel et al, 1999;Molloy and Scott, 2001;Ray et al, 2002). These studies have focused on neural tube defects and craniofacial abnormalities, due to their ease of detection at birth and visual ascertainment criteria (Berry and Li, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…These associations are consanguinity with monogenic disorders, high maternal age with chromosomal anomalies [12, 13], low maternal age with gastroschisis [16, 17], antiepileptics (valproic acid) with neural tube defects [14, 15, 18]and diabetes with cardiovascular defects [19, 20]. …”
Section: Discussionmentioning
confidence: 99%